Evidence for New Endothelial Cell Binding Sites on Fibrinogen - Smith, Richard A.; Rooney, Michael M.; Lord, Susan T.; Mosesson, M. W.; Gartner, T. Kent (Thrombosis and Haemostasis, 2000)
In vitro assays were used to characterize adhesion of human aortic, microvascular and umbilical vein endothelial cells to various forms of immobilized fibrinogen. All three types of endothelial cells adhered to fibrinogen in a manner that was independent of the Aα-chain 572-574 RGD cell binding site. In fact, all three adhered to a fragment of the molecule which is composed of only one D domain (D1) of fibrinogen. A time course study revealed that extensive adhesion of endothelial cells on the ligand coated surface occurred between one and two hours incubation. The anti-fibrinogen γA-chain monoclonal antibody 4A5 as well as 4A5 Fabs, blocked adhesion of endothelial cells to fibrinogen, not vitronectin. The inhibitory effects of 4A5 seemed to be indirect because the endothelial cells adhered to the recombinant fibrinogen γ407 (which lacks the γ-chain AGDV sequence of the carboxyl terminal 4A5 binding site) as well as they did to normal recombinant fibrinogen. A recombinant fibrinogen lacking the γ-chain AGDV sequence, containing RGE in place of RGD at the γ-chain 572-574 and 95-97 positions, also supported endothelial cell adhesion. The anti-αvβ3 antibody, LM609, blocked adhesion of endothelial cells to fibrinogen. The peptide GRGDSP inhibited endothelial cell adhesion on fibrinogen and vitronectin. These results demonstrate that αvβ3 mediated adhesion (attachment and spreading) of HUVECs to fibrinogen may use a site in the D domain of fibrinogen and is not dependent on the Aα-chain RGD (95-97 and 572-574) sequences, as has been shown in shorter term (where cells were rounded) experiments, or the γA-chain 408-411 cell binding sites. Thus, the data reveal the existence of another unidentified site(s) on fibrinogen which can support the irreversible adhesion (attachment and spreading) of endothelial cells.
Keywords: Fibrinogen; HUVECs; adhesion; αvβ3; RGD